The effect of varying pH levels on the growth ofbTeraselmis sp. - Taglorin, Christie Z. (2017.)
Microalgal cultivation has attracted much attention in recent years due to its commercial and industrial applications. In the field of aquaculture, Tetraselmis sp., for instance, is one of the many species of microalgae that are being utilized and studied for feed purposes. This green marine microalga is identified as one of the ideal species to be cultured since it can tolerate various environmental conditions including pH. In this study, Tetraselmis sp. Was cultured in varying pH levels to determine its effect on the growth of the microalgae. The growth rate of Tetraselmis sp. Was calculated from the daily measurement of the algal cell density measured as cells/ml. using a hemocytometer and microscope as tools. The result of the 6-day experiment and algal density monitoring showed that at pH 7.5 the Tetraselmis sp. Culture obtained the highest algal density and growth rate. Whereas, the Tetraselmis sp. Cultured at the pH level of 7.0 and 9.0 obtained the lowest algal density and growth rate. Based on the statistical analysis used (oneway ANMOVA), the varying levels of pH had no significant effect. (p>0.05) on the growth of the Tetraselmis sp. Culture, supported by the fact that Tetraselmis sp. Can tolerate varying conditions of their environment
Thesis (Bachelor of Science in Fisheries) Institute of Aquaculture, College of Fisheries and Ocean Sciences, University of the Philippines Visayas.
Keywords: Aquaculture; Marine microalgae; pH; Tetraselmis